2020
DOI: 10.1103/physreva.102.023519
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transitions of optical patterns in atomic gases with microwave-controlled Rydberg interactions

Abstract: Spontaneous symmetry breaking and formation of self-organized structures in nonlinear systems are intriguing and important phenomena in nature. Advancing such research to new nonlinear optical regimes is of much interest for both fundamental physics and practical applications. Here we propose a scheme to realize optical pattern formation in a cold Rydberg atomic gas via electromagnetically induced transparency. We show that, by coupling two Rydberg states with a microwave field (microwave dressing), the nonloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…k cr = [Gρ b /(Rρ b − 1/4)] 1/2 , such that ω becomes imaginary when k > k cr , corresponding to the occurrence of modulation instability (MI). Note that the MI is unique for the defocusing nonlocal medium and crucial for the formation of various optical patterns [74]. In the long wavelength limit (k → 0), the dispersion relation takes the form…”
Section: Sound Propagationmentioning
confidence: 99%
“…k cr = [Gρ b /(Rρ b − 1/4)] 1/2 , such that ω becomes imaginary when k > k cr , corresponding to the occurrence of modulation instability (MI). Note that the MI is unique for the defocusing nonlocal medium and crucial for the formation of various optical patterns [74]. In the long wavelength limit (k → 0), the dispersion relation takes the form…”
Section: Sound Propagationmentioning
confidence: 99%
“…Note that, when deriving the above equations, we have assumed that the probe field is a spatial light beam, i.e., its envelopes are stationary (i.e., Ω pj is time-independent everywhere). Such assumption is valid for the probe field having a large time duration, so that a continuous-wave (CW) approximation can be applied [7,8,16]; moreover, the spatial width of the envelopes in z direction is assumed to be large so that a local approximation in the z direction for the effective nonlinear interaction potentials between photons [7,8,14,16] (or called spatial response functions) N jl (r ′ − r) can be made, which gives…”
Section: Coupled Nonlocal Nls Equationsmentioning
confidence: 99%
“…Based on such nonlocality, Sevincli et al [8] showed that a hexagonal optical pattern can spontaneously form through a modulational instability (MI) of plane-wave probe field in a ladder-shaped three-level Rydberg gas (Rydberg-EIT) with repulsive Rydberg-Rydberg interaction. Recently, it was demonstrated that a structural phase transition of optical patterns from a hexagonal lattice to two types of square lattices may occur in an EIT-based Rydberg gas with a microwave dressing between two Rydberg states [16]. These investigations enriched our understanding on the MI and related pattern formation in systems with repulsive (or with both repulsive and attractive) Kerr nonlinearities, which are topics explored in different physical systems by many research groups, from which new pattern formation mechanisms for conservative nonlocal nonlinear systems were found in recent years [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%